Respuestas
Respuesta dada por:
1
Aplicas.
Productos Notables.
(a - b) =
a² - 2ab + b²
(- 5s + 2v)² =
(2v - 5s)² =
(2v)² - 2(2v)(5s) + (5s)² =
2²v² - 20vs + 5²s² =
4v² - 20vs + 25s²
Respuesta.
4v² - 20vsv+25s²
yooo10:
Gracias
Respuesta dada por:
0
Productos Notables.
(a - b) =
a² - 2ab + b²
(- 5s + 2v)² =
(2v - 5s)² =
(2v)² - 2(2v)(5s) + (5s)² =
2²v² - 20vs + 5²s² =
4v² - 20vs + 25s²
Respuesta.
4v² - 20vsv+25s²
(a - b) =
a² - 2ab + b²
(- 5s + 2v)² =
(2v - 5s)² =
(2v)² - 2(2v)(5s) + (5s)² =
2²v² - 20vs + 5²s² =
4v² - 20vs + 25s²
Respuesta.
4v² - 20vsv+25s²
Preguntas similares
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años